AN ANALYSIS OF STUDENT’S ERROR IN WRITING DESCRIPTIVE TEXT - Rika Rahmawati Suryana (La Tansa Mashiro, 2019)
The paper aims to find out the most typical errors and sources of error on students’ descriptive writing of the tenth grade of SMAN 3 Rangkasbitung. This study was conducted in the SMAN 3 Rangkasbitung, the 1st semester of the school year 2014-2015. The population of the research was 30 students from one class of the tenth grade of SMAN 3 Rangkasbitung and the sample was taken 30 students. The writer uses a descriptive qualitative approach and error analysis based on the aspect. As the result, the researcher found that the students made 78 errors in their descriptive writings. The errors occurred in all types of errors investigated. There are verb tense, omit a word, spelling, add a word, capitalization, word choice, word order, singular – plural, word form, article. The sources of error was also mostly due to interlanguage transfer. Therefore, the teachers should be more focus on teaching of verb tense then must give remedial teaching after identifying students’ error in writing also the teachers can teach students to more practices on writing.